Approaches To Detect Cyber Crime On Social Media - P.Varsha (International Journal of Advanced Science and Technology, 2020)
In the recent years, cybercrime and its forms have grabbed the attention. Due to the immersive growth of internet, users made a platform to propagate unwanted activities. Cyber bullying is wide spread across social media and has adverse consequences. It results in humiliation of victim and leads to ill health. Seeking cyber bullying as a challenging task, a pool of robust methods are emerging in its detection. This study presents a detailed survey of the methods and techniques involved in this field. This survey relates in providing Data collection and data sets, Pre-processing techniques, Feature extraction and selection techniques, Classification methods and their results in automatic detection of cyber bullying.